2009
DOI: 10.1029/2008wr007643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kinetic mass transfer and transient flow conditions on widening mixing zones in coastal aquifers

Abstract: [1] The width of a mixing zone between freshwater and seawater is important primarily because it directly reflects the extent of mixing and the growth and decay of the mixing zone indicates changes of the flow regime and water exchange between freshwater and coastal seawater. Wide mixing zones have been found in many coastal aquifers all over the world. However, the mechanisms responsible for wide mixing zones are not well understood. This work examines the hypothesis that kinetic mass transfer coupled with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…Michael et al [2005] showed that these oscillations can lead to seasonal discharge of saline water from a CUA. Seasonal oscillations in the DZ location can also lead to significant widening of the DZ and thus expansion of the STE particularly in more heterogeneous aquifers and where salt gets trapped in non-mobile pores [Lu et al, 2009].…”
Section: Rechargementioning
confidence: 99%
“…Michael et al [2005] showed that these oscillations can lead to seasonal discharge of saline water from a CUA. Seasonal oscillations in the DZ location can also lead to significant widening of the DZ and thus expansion of the STE particularly in more heterogeneous aquifers and where salt gets trapped in non-mobile pores [Lu et al, 2009].…”
Section: Rechargementioning
confidence: 99%
“…Moreover, Michael et al [2005] used hydraulic gradient measurements to conclude that the inland seasonal hydrologic cycle causes a seasonal mixing zone movement in coastal aquifers. Finally, an alternative explanation for broad mixing zones observed in coastal aquifers has been provided by Lu et al [2009], who showed that the movement of the mixing zone combined with kinetic mass transfer effects may significantly widen the mixing zone.…”
Section: Introductionmentioning
confidence: 99%
“…The mass transfer rate coefficient controls how quickly mass is exchanged between the mobile and immobile domain. Our previous study found that when the retention timescale and the period of freshwater‐level fluctuations become comparable, the mixing zone thickness is maximized [ Lu et al , 2009]. Three timescale ratios are considered: 0.01, 1 (base model) and 100.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the aquifer storage and recovery (ASR) strategy may have a low recovery ratio in a dual‐domain coastal aquifer due to the mobilization of solutes initially residing in immobile domains [ Eastwood and Stanfield , 2001; Culkin et al , 2008]. Our previous study has found that kinetic mass transfer combined with periodic movement of the mixing zone may significantly enhance mixing and result in a much thicker mixing zone, as shown in Figure 1 [ Lu et al , 2009]. Prior to our finding, thick mixing zones were usually characterized by large dispersion coefficients or assuming highly heterogeneous hydraulic conductivity fields, both of which may not be realistic [ Dagan , 2006].…”
Section: Introductionmentioning
confidence: 99%